DLP 3D printing porous β-tricalcium phosphate scaffold by the use of acrylate/ceramic composite slurry. Issue 15 (1st August 2021) - Liu, Sa; Mo, Lina; Bi, Gangyuan; Chen, Shenggui; Yan, Diwei; Yang, Junzhong; Jia, Yong-Guang; Ren, Li
Abstract: Digital light processing (DLP) 3D printing has been utilized to fabricate controlled porous β-tricalcium phosphate (β-TCP) scaffolds, which promote cell adhesion and angiogenesis during bone regeneration. However, the current limitation of DLP 3D printing for the fabrication of β-TCP scaffold is how to prepare a low viscosity ceramic slurry and remove the toxicity of residual non-polymerized slurry. The present study has developed a low viscosity ceramic slurry system by mixing β-TCP with photosensitive acrylate resin, and the viscosity of slurry is about 3 Pa s and the solid content of β-TCP can be as high as 60 wt%. After optimizing the ratio of slurry, printing, degreasing and sintering processes, the maximum compressive strength of the DLP printed scaffolds reaches up to 9.89 MPa, while the porosity keeps ca. 40%. According to the proliferation of cells, it confirms the preserved biocompatibility of DLP-fabricated β-TCP scaffolds. These porous scaffolds made by DLP 3D printing technology is of great significance for bone regeneration, and will also help to expand the application of DLP technology in biomedical field.